A cross sectional study investigating dynamic balance when stepping to targets in children with cerebral palsy compared to typically developing children - Rapson, R.; Latour, Jos; Carter, B.; Pitsouni, V.; Marsden, J.F. (2023)
Background: Children with Cerebral Palsy (CP) have altered anticipatory postural adjustments (APAs) during gait initiation. These APAs may affect dynamic balance in tasks such as stepping. Research questions: How are APAs in children with CP affected during stepping to precise targets? How do children with CP modulate APAs when stepping to medial and lateral targets? What is the association between APAs and symptom severity, movement quality and impairment profile? Method: Children undertook a stepping task to laterally and medially placed targets with either leg, in a randomised order. Movement of the centre of pressure (COP) and markers at the pelvis and foot were measured via a force plate and 3D motion analysis. Motion of the centre of mass (COM) was estimated via pelvic markers. APAs were assessed prior to leading leg lift-off in medio-lateral and antero-posterior directions. Stepping error was calculated. Baseline characteristics of children with CP included Gross Motor Function Measure (GMFM), Quality Function Measure (QFM), leg muscle hypertonia (Tardieu test) and strength (manual dynamometry). Results: Sixteen ambulant children with CP (12.2 years ± 2.2) and 14 typically developing (TD) children (11.6 years ± 2.9) were assessed. In children with CP, APAs in the medio-lateral direction were 20–30% smaller. Children with CP were less able to modulate their APAs with steps to medial and laterally placed targets, than TD children. Medio-lateral COP motion was associated with movement quality assessed by QFM subsections, GMFM (correlation coefficient r = 0.66–0.80) and hip abductor strength (r = 0.75). Antero-posterior APAs were significantly smaller when stepping with the non-paretic leg in children with CP. APA size was positively related to the length of the contralateral, paretic gastrocnemius (r = 0.77). Stepping error was higher in children with CP and inversely correlated to the size of the medio-lateral APA. Discussion: Children with CP show smaller medio-lateral APAs especially when stepping to medially placed targets. APA size may be limited by proximal muscle strength and gastrocnemius length.